Scale development for measuring the inclusiveness of entrepreneurship among women - Senthilnathan, Saranya; Kaliyaperumal, Chandrasekar (Review of Management, Accounting, and Business Studies, 2026)
This study developed and validated a comprehensive measurement scale to assess inclusiveness in women’s entrepreneurship with a focus on marginalized and rural communities in Tamil Nadu. Drawing on the Capability Approach and Institutional Theory, it used a rigorous two-phase methodology involving extensive literature review and empirical validation with data from 376 women entrepreneurs. Exploratory and confirmatory factor analyses identified four core dimensions of inclusiveness: financial, technological, managerial, and marketing inclusion. The final measurement model demonstrated strong internal consistency, reliability, and construct validity across all dimensions. Notably, technological and marketing inclusion were the most influential factors, highlighting the pivotal roles of digital access and market connectivity in sustaining women-led enterprises. This validated scale serves as a diagnostic tool for researchers, policymakers, and practitioners to evaluate entrepreneurial programs and formulate targeted, inclusive interventions. By operationalizing inclusiveness comprehensively in the context of women’s entrepreneurship, the study fills a critical literature gap and provides an empirically sound instrument applicable in developing country contexts. It enhances understanding of the impact of government schemes on women entrepreneurs and supports the design of gender-responsive and regionally inclusive economic policies to foster entrepreneurship growth and socio-economic development in Tamil Nadu.